2010
DOI: 10.1152/jn.00554.2010
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Organization of Excitatory and Inhibitory Commissural Connections in the Superior Colliculi and Their Functional Roles in Saccade Generation

Abstract: Takahashi M, Sugiuchi Y, Shinoda Y. Topographic organization of excitatory and inhibitory commissural connections in the superior colliculi and their functional roles in saccade generation. J Neurophysiol 104: 3146 -3167, 2010. First published October 6, 2010 doi:10.1152/jn.00554.2010. Our electrophysiological study showed that there are topographic connections between excitatory and inhibitory commissural neurons (CNs) in one superior colliculus (SC) and tectoreticular neurons (TRNs) in the opposite SC. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 65 publications
2
39
0
Order By: Relevance
“…Although such activation is weak (after all, errors occur on only approximately 20% of all tactile trials), its initial oculomotor representation (e.g., within the SC) enables interactions with the oculomotor representation of the visual stimulus. Theoretical and experimental studies have suggested that interactions within the SC are governed by topographically dependent mechanisms enforcing local excitation and distal inhibition (Arai and Keller 2005;Dorris et al 2007;Grossberg et al 1997;Marino et al 2011;McPeek and Keller 2002;Meredith and Ramoa 1998;Munoz and Istvan 1998;Sooksawate et al 2011;Takahashi et al 2010), potentially by mechanisms of divisive normalization across the population (Ohshiro et al 2011). We speculate that weak activation of opposing SC shortly after presentation of visuotactile stimuli in the crossed posture leads to mutual inhibition via the spatial principle (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Although such activation is weak (after all, errors occur on only approximately 20% of all tactile trials), its initial oculomotor representation (e.g., within the SC) enables interactions with the oculomotor representation of the visual stimulus. Theoretical and experimental studies have suggested that interactions within the SC are governed by topographically dependent mechanisms enforcing local excitation and distal inhibition (Arai and Keller 2005;Dorris et al 2007;Grossberg et al 1997;Marino et al 2011;McPeek and Keller 2002;Meredith and Ramoa 1998;Munoz and Istvan 1998;Sooksawate et al 2011;Takahashi et al 2010), potentially by mechanisms of divisive normalization across the population (Ohshiro et al 2011). We speculate that weak activation of opposing SC shortly after presentation of visuotactile stimuli in the crossed posture leads to mutual inhibition via the spatial principle (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…These correlated changes suggest that the involvement of the dSC in the triggering and dynamics of saccades rest upon shared processes (see also Figures 3C and 5A in Sparks et al (1990) as well as Stanford et al (1996) for comparable observations using electrical microstimulation techniques). The changes that affect contralesional saccades likely result from a diffusion of muscimol toward the site encoding the tested peripheral target (see Methods) whereas those altering ipsilesional saccades could result from disinhibition of neurons in the opposite dSC via inhibitory inter-collicular connections (Takahashi et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…GABA-ergic projection via the intercollicular commissure (Appell and Behan 1990;Munoz and Istvan 1998;Sooksawate et al 2011;Takahashi et al 2010). Likewise, recent studies have demonstrated that the substantia nigra pars reticulata (SNr), in addition to its well-known inhibitory projection to the ipsilateral SC (Chevalier et al 1984;Hikosaka and Wurtz 1983;Karabelas and Moschovakis 1985;May and Hall 1984), provides a crossed inhibitory input to the opposite SC Liu and Basso 2008).…”
Section: Discussionmentioning
confidence: 99%